KESINTASAN PASIEN DENGAN METASTASIS LEPTOMENINGEAL YANG DIRAWAT DI BAGIAN NEUROLOGI RUMAH SAKIT KANKER DHARMAIS DAN RSUPN DR CIPTO MANGUNKUSUMO - Elsa Susanti,* Rini Andriani,** Tiara Aninditha,*** Henry Riyanto Sofyan*** (Neurona Majalah Kedokteran Neuro Sains, 2020)
INTRODUCTION LEPTOMENINGEAL METASTASIS IS A CONDITION WHERE MALIGNANT CELLS SPREAD TO THE LEPTOMENING AND SUBARACHNOID SPACE THIS IS AN EMERGENCY STATE WITH INCIDENT TENDS TO INCREASE EACH YEAR PROGNOSIS IS VERY POOR AND SURVIVAL RATE IS ONLY 1015 WEEKS